Enacting Algorithms Through Encoding and Decoding Practices - Pronzato, Riccardo (Italian Sociological Review, 2024)
In the field of digital sociology, debates continue about the best strategies to analyse the social role of algorithms, their design and uses, as well as their implications. To contribute to this conversation, this paper bridges a practical approach to culture – which considers culture as an outcome of social activities – with the tradition of cultural studies – which frames culture as a set of practices in the construction and interpretation of media messages and technological artifacts. Specifically, I focus on how Nick Seaver’s “algorithms as culture” approach intersects with Stuart Hall’s “Encoding/Decoding” model and the following applications to algorithmic media of different authors. Through this analysis, I argue that algorithms are culturally enacted by the encoding and decoding practices of their producers and end users. Thus, algorithms are considered as brought into being by the activities underlying their design, as well as by their uses, analyses, and interpretations. Furthermore, I propose different methodological strategies to analyse how encoding/decoding activities culturally enact algorithms within the social realm.